Deus Ex Algorithmo: Narrative Form, Computation, and the Fate of the World in David Mitchell's Ghostwritten and Richard Powers's The Overstory. - Caracciolo, Marco (Contemporary Literature)
An excerpt from the article "Ghostwritten" by David Mitchell and 'The Overstory' by Richard Powers issue of "Contemporary Literature" is presented focusing on technological challenge and transforming the lives of general public through the development of Internet and mobile technologies.